Assessment of GPS L1/Galileo E1 interference monitoring system for the airport environment - Isoz, Oscar; Akos, Dennis; Lindgren, Tore; Sun, Chih-Cheng; Jan, Shau-Shiun (Luleå tekniska universitet, EISLAB, 2011)
How does the GPS Ll spectrum look like at a commercial airport? How frequently do radio frequency interference (RFI) incidents occur? To answer this, the GPS Ll/Galileo El band was monitored at two different airports for an extended period of time. The monitor stations continuously recorded the noise level using the automatic gain control (AGC) in the frontend. Also, the raw intermediate frequency (IF) signal was recorded at regular intervals as well as when the AGC level dropped below a certain threshold. In this paper the analysis of long-term measurements of the spectrum and AGC level at Luleå Airport outside Luleå, Sweden, and Kaohsiung International Airport in Kaohsiung City, Taiwan, is presented. The results shows that RFI incidents did occur at both airports, although more frequent at Kaohsiung International Airport. The measurements also show that the AGC level is useful in systems monitoring the RFI environment. Importantly, the measured data could be utilized for analyses toward the future introduction of GBAS for civil aviation authorities. How does the GPS L1 spectrum look like at a commercial airport? How frequently do radio frequency interference (RFI) incidents occur? To answer this, the GPS L1/Galileo E1 band was monitored at two different airports for an extended period of time. The monitor stations continuously recorded the noise level using the automatic gain control (AGC) in the frontend. Also, the raw intermediate frequency (IF) signal was recorded at regular intervals as well as when the AGC level dropped below a certain threshold. In this paper the analysis of long-term measurements of the spectrum and AGC level at Luleå Airport outside Lueå Sweden, and Kaohsiung International Airport in Kaohsiung City, Taiwan, is presented. The results shows that RFI incidents did occur at both airports, although more frequent at Kaohsiung International Airport. The measurements also show that the AGC level is useful in systems monitoring the RFI environment. Importantly, the measured data could be ...